HOW EFFECTIVE IS THE MODIFIED ALTMAN MODEL IN PREDICTING FINANCIAL FAILURE IN ECONOMIC INSTITUTIONS- AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI BANKS LISTED ON THE IRAQI STOCK EXCHANGE FOR THE PERIOD (2018-2022) / PROPOSED MODEL - Sheimaa Hadi Nama Alkhafaji; Zainab Hadi Neamah (Scholars Digest Publishing, 2024)
The current research aims to highlight the importance of using the Altman's Z-score model in predicting the performance failure of economic institutions, the research also aims to enhance the efficiency of work within Iraqi economic institutions based on the model from global quantitative models, this research follows the descriptive research model to assess the levels of financial failure by looking at the annual financial reports published for the sample banks, and how this assessment will affect the performance of banks when making financing and investment decisions in the near future. Ten banks were selected (Sumar Commercial Bank, Iraqi National Bank, Iraqi Commercial Bank, Gulf Commercial Bank, Iraqi Investment Bank, Middle East Investment Bank, Mosul Development and Investment Bank, Iraqi Union Bank, Basra International Bank, and Al-Warka Bank). For the period (2018-2020), the analytical descriptive method was adopted to reach the research outputs, where the research adopted statistical methods to analyze the data in the statistical program JASP (weighted arithmetic mean, standard deviation and ANOVA to test the F statistic to know the quality of the standard model, and finally the research variables were tested by means of the P-value test). The research found that out of ten selected banks, two commercial banks are located below the failure zone, three banks are located in the financial failure zone and the remaining five banks are located outside the financial failure zone. This research also found that Altman's Z-Score model helps economic institutions in stabilizing and sustaining within the markets, and helps them in making strategic decisions. The research recommends the need to review policies within economic institutions to increase the forecasting horizon of the financial failure model to more than one year, as most forecasting models fail to accurately predict the occurrence of failure after more than one year, and the accuracy of the model tends to decrease as the forecasting curve steepens.
Keywords: financial failure, financial failure models, modified Altman model, financial failure prediction, economic institutions.